Hankel inequalities for bounded turning functions in the domain of cosine Hyperbolic function - Muhammmad Ghaffar Khan; Wali Khan Mashwani; Lei Shi; Serkan Araci; Bakhtiar Ahmad; Bilal Khan (AIMS Mathematics, 2023)
In the present article, we define and investigate a new subfamily of holomorphic functions connected with the cosine hyperbolic function with bounded turning. Further some interesting results like sharp coefficients bounds, sharp Fekete-Szegö estimate, sharp $ 2^{nd} $ Hankel determinant and non-sharp $ 3^{rd} $ order Hankel determinant. Moreover, the same estimates have been investigated for 2-fold, 3-fold symmetric functions, the first four initial sharp bounds of logarithmic coefficient and sharp second Hankel determinant of logarithmic coefficients fort his defined function family.